Determination of Eight Microcystins in Water by Ultra-High Performance Liquid Chromatography-Tandem Mass Spectrometry - ZHANG Panwei; LANG Hang; DING Xiangyi; ZHAO Xiaohui; LI Kun; WAN Xiaohong; LI Zheng (Renmin Zhujiang)
Microcystins (MCs) are a common class of hepatotoxins mainly produced upon the apoptosis of freshwater blue-green algae and are highly poisonous to human beings and aquatic life.It is of great significance to establish an accurate and rapid detection method of MCs for the safety of drinking water.Therefore,this study optimizes conditions such as solid-phase extraction,chromatography,and spectrometry and develops the simultaneous detection method of ultra-high performance liquid chromatography and tandem mass spectrometry (UPLC-MS/MS) to detect eight MCs (LR,RR,YR,WR,LW,LA,LF,and LY) in water.For this method,the limit of detection and the limit of quantitation are 0.002~0.006 μg/L and 0.006~0.018 μg/L,respectively;the recovery ratios are between 85.3% and 107.5%,and the relative standard deviation (RSD) is less than 11%.This method can provide technical support for the daily detection of MCs in surface water.